2014
DOI: 10.2169/internalmedicine.53.2301
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Artery Aneurysm Diagnosed on 3D-CT

Abstract: A 71-year-old woman was admitted to our hospital due to hemoptysis. She had a history of hemoptysis occurring five years previously, for which she had been closely followed without treatment. A chest X-ray showed consolidation in the left lower lung field (Picture 1), and chest CT demonstrated abnormal blood vessels in the left lower lobe (Picture 2) and enlargement of the left bronchial artery caused by two aneurysms (Picture 3, 4). One of the aneurysms was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Among these cases, 5 procedures were unsuccessful and were succeeded immediately with surgical intervention or a second TAE. [36] After temporal success in another 5 patients, refilling of the aneurysm on follow-up imaging and recurrence of symptoms was documented. [711] The reasons for failure of a TAE were complicated, but may be related to the greatly enlarged bronchial artery and revascularization by collateral arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these cases, 5 procedures were unsuccessful and were succeeded immediately with surgical intervention or a second TAE. [36] After temporal success in another 5 patients, refilling of the aneurysm on follow-up imaging and recurrence of symptoms was documented. [711] The reasons for failure of a TAE were complicated, but may be related to the greatly enlarged bronchial artery and revascularization by collateral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…[3,10,17,20–28] These patients were slightly younger (mean age, 50.7 years) than cases of single BAA reported in the literature (mean age, 59.3 years). We also observed that patients with >1 BAA were significantly more likely to be female (80%) than male ( χ 2 test, P  = 0.034).…”
Section: Discussionmentioning
confidence: 99%
“…21 The presentations of BAA are related to the size, location, and complications. The most common symptom of multiple BAAs is hemoptysis, 10 -12,14,17,18 found in 50% of the cases. Other symptoms include cough, 5 dyspnea, 12 chest pain, 7 dysphagia, 5 back pain, 16 and hoarseness.…”
Section: Discussionmentioning
confidence: 99%